Dynamics Dynamics of Islamic Education and Indigenous Culture in Lombok: A Historical Study of Adaptation, Acculturation, and Assimilation - Suprapto, Suprapto; Khusniyah, Nurul Lailatul; Thoib, Ismail; Iswar, Nabila Salsabila (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
Islamization in Lombok demonstrates the dynamic interaction between Islamic education, particularly through the pesantren system, and the local culture of the Sasak people. Previous studies have emphasized the classical role of pesantren as centers for the transmission of turats knowledge. Still, they have been limited in explaining how pesantren have transformed through processes of adaptation, acculturation, and assimilation in the modern context. This study aims to analyze the integration of local cultural values with Islamic education in Lombok, while also formulating a model of glocal Islamic pedagogy that is relevant to the demands of the 21st century. This research employs a qualitative approach using ethnographic and historical methods. Data was collected over four months through semi-structured interviews with religious scholars, traditional leaders, and community members, participatory observation at pesantren in Central and West Lombok, and analysis of documents from historical archives and relevant literature. Data analysis was conducted thematically through reduction, presentation, and verification using triangulation of sources and methods. Preliminary findings reveal three main stages of Islamization in Lombok: adaptation through the contextualization of Islamic teachings and hybrid pesantren curricula; acculturation through the harmonization of Sasak traditions such as Wayang Sasak with Islamic education; and assimilation, marked by the full integration of Islamic values into the local socio-cultural identity. This study contributes to the development of Islamic education theory by offering a “glocal Islamic pedagogy” framework that combines classical heritage with contemporary competencies. These findings are expected to support the development of contextual and sustainable Islamic education models that are locally relevant yet globally competitive.